OPTIMALISASI UMKM MELALUI PELATIHAN KEUANGAN DAN DIGITALISASI - Listiani, Nur; Pariyono, Pariyono; Amin, Moh. Solikul; Syamsudin, Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting the national economy; however, they continue to face challenges in financial management, digital technology adoption, and electronic payment systems. This community service program aims to enhance the capacity of MSME actors through basic financial training, digital marketing strategies, and the implementation of QRIS as a non-cash payment method. The program was carried out through several stages, including observation, training, mentoring, and evaluation. The results indicate an improvement in financial literacy, skills in recording daily transactions and preparing simple financial reports, utilization of social media for business promotion, and the application of QRIS, which has a positive impact on transaction efficiency and increases customer trust. This program has proven effective in encouraging MSMEs to adopt more professional business management practices, modern operations, and adaptability to technological developments.